Identifikasi Data Reservoir Dengan Menggunakan Pemodelan Software RFD Untuk Mengetahui Production Forecast Rate Di Sumur J Lapangan A - Edy Soesanto; Eko Prastio; Jessica Abidin (Department of Petroleum Engineering, 2022)
Reservoir simulation is a process of mathematically modeling reservoir conditions by integrating various existing data (geology, geophysics, petrophysics, reservoirs, etc) to obtain reservoir performance in well conditions so that the purpose of reservoir simulation is to determine the current and future reservoir performance to estimate the rate of oil production (production forecast rate). Rapid technological developments encourage experts to create computer software that is used as a simulation tool. The method in this study uses reservoir modeling simulation software. The production forecast rate in this reservoir model is carried out for 2 years by only adding one production well in the reservoir area that has not been drained, namely infill well A. This shows that the oil production rate continues to decrease but increases the cumulative oil production. The cumulative oil production produced by well A was 33,80 STB in 2014 with an average increase of 12%. Therefore, it is necessary to evaluate the reservoir model after 2014 in detail the value of the data again so that the reservoir simulation process for the next forecast gets good oil production results.